Life Cycle Assessment of olive oil production in Greece. (15th April 2015) - Tsarouhas, P.; Achillas, Ch.; Aidonis, D.; Folinas, D.; Maslis, V.
Abstract: Agricultural production is a sector with high socio-economic significance and key implications on employment and nutritional security. However, the impacts of agrifood production and consumption patterns on the environment are considerable, mainly due to the demand of large inputs of resources. This paper presents a case study of olive oil production in Greece, an important agri-product especially for countries in the Mediterranean basin. Life Cycle Assessment has been used to quantify the environmental performance of olive oil production. Fourteen sub-systems of the overall olive oil production are investigated. All key parameters that are associated with the life cycle of olive oil production are studied and environmental "hotspots" are diagnosed. Cultivation of olive trees and production of olive oil are the sub-systems that are responsible for the majority of the environmental impacts and thus any effort to minimize the overall life cycle impact from olive oil production should include them.